O desenvolvimento profissional dos professores iniciantes egressos do curso de Licenciatura em Pedagogia : um estudo de caso - França, Márcia Socorro dos Santos (2016)
This Master’s thesis investigates an unexplored theme on the national research scenario: the professional development of beginning teachers graduated in Pedagogy. This study is linked to the Master Degree Program in Education of Federal University of Mato Grosso, in Rondonópolis city. It was developed into the line of research Teacher Education and Educational Public Policies and it is a result of several discussions promoted by the researchers group InvestigAção. This study understands teacher education as one of the leading aspects of professional development which must be constantly improved along teachers career. Thus, we consider the beginning of teaching career a fundamental part of this process. Such period is featured by doubts, anguishes and fears, attempts of adjustment, interactions and decisionmaking about teaching career. The main goal of this research was to investigate what beginning teachers graduated in Pedagogy say about their professional development after their participation on the OBEDUC/UFMT project. It presents a qualitative approach based on a case study. Some procedures and data collection instruments such as observation, document analisys, analisys of autobiographical narratives (specially memorial) and semi-structured interviews were used to develop this research. The study was guided by the following questions: What are the needs pointed by the beginning teachers participants of the OBEDUC/UFMT project? What do these teachers say about this education project? How do they associate the project to their professional development? Four teachers of the initial years of elementary school cooperated with this study. They were chosen because they graduated recently in pedagogy at UFMT/CUR and they had less than five years of experience on their career as teachers at that time. The data were collected in some educational meetings promoted at UFMT/CUR and also in four schools: two of them were municipal schools and two of them were state schools. The results point out that the continuing education program offered by the OBEDUC/UFMT project contributes to the professional development of teachers throught the promotion of several reflections about their pedagogical practices and teaching career.